Answer:
The answer to your question is: 83 + 6[tex]\sqrt{35}[/tex]
Step-by-step explanation:
This is a square of a binomial.
(2[tex]\sqrt{5}[/tex] + 3[tex]\sqrt{7} )^{2}[/tex]
1.- Square of the first term
( 2[tex]\sqrt{5} )^{2}[/tex] = 4(5) = 20
2.- Twice the product of the two terms
(2)(2[tex]\sqrt{5} )[/tex](3[tex]\sqrt{7} )[/tex] = 6[tex]\sqrt{35}[/tex]
3.- Square of the second term
(3[tex]\sqrt{7)})^{2}[/tex] = 9(7) = 63
4.- Write the solution
20 + 6[tex]\sqrt{35}[/tex] + 63
83 + 6[tex]\sqrt{35}[/tex]